KONSTRUKSI SOSIAL BUDAYA BANYU PANGURIPAN DALAM AGAMA KATOLIK - Hamsah, Ustadi (Religi: Jurnal Studi Agama-agama, 2013)
The origin of the history of religion is closedly related to water re- sources. It had been known that, since the beginning people always lived in fertile river valley or other places that they could acquire water resources. These phenomena can be vividly seen in the history of ancient Egypt, Mesopotamia, Babylonia, Phunisia, Accadia, Assyria, and so forth. Born in the fertile valleys, adherents of those religious traditions worshipped the godess as a â€œgod of fertilityâ€. They associ- ated the concept of fertility with the godesses. This tradition was not only preserved by ancient tradition but also perpetuated by new reli- gious tradition such as early Catholicism as well as other religious traditions. In relation to such a notion, this article intends to explore the phenomenon of interrelation between the pilgrimage tradition in Catholicism and the concept of water and role of Mary as a â€œholy motherâ€. Both water and Mary have correlated to some holy places that followers of Catholicism use to visit.